Da uniformização da interpretação de lei no sistema dos juizados dos estados e do Distrito Federal (art. 18 da lei n. 12.153/2009) - Steinberg, José Fernando (2012)
Handles this dissertation analyzing the incident uniform interpretation of law, under the special courts of the States and Federal District, in accordance positivized by art. Federal Law N. 18 12.153/2009, which established the special courts of the Exchequer. At first, it was shown a little about the general philosophy of specialized courts, and the peculiarities of his appeal system, settled exclusively by judges of first instance, as a rule, without being given access to the courts of justice. But despite the excellent results in terms of speed, until 2009, no attention had been paid to the possibility of delivery of disparate decisions by numerous colleges around the country considering the impossibility of bringing the special appeal for the preservation of the unity of interpretation of federal law (No 203 Summary, STJ), and low viability of the extraordinary appeal, reserved for strictly constitutional and representative issues. As a result of that, people in general were submitted to a not very coherent and harmonious system, although rapid, as seen in the famous case of telephone operators tried by the Supreme Court in RE 571572, rapporteur of the minister Ellen Gracie. Hence the need to create a mechanism for the preservation of the jurisprudence of the superior courts. It was demonstrated the beneficial effect of the adoption of binding precedents, but the serious prejudice to the principle of speed in the creation of a "special feature" stealth incident intra muros. Accordingly, it was analyzed the functioning of the real asset, owing to the peculiarities shown in the new Law 12.153/2009, which is not limited to the discipline of the courts of the Exchequer city and state, but that spreads throughout the system rite summary. Still, attempts aim to strengthen the culture of the foregoing, as seen, for example, the new incident resolution demands the constant repetitive design of the new CPC, approved by the Senate, but, pending consideration by the House of Representatives (PL n . 166/2010 or n. 8.046/2010).Even the President of the Supreme Court is facing the Brazilian bankruptcy appellate system, which can be prevented or remedied by the SGP No 15/2011, of his own intellectual, and proposes that the anticipation of a final and unappealable decisions on the occasion of delivery of the second degree. The approximation of systems of common law and civil law, with the increasing objectification of the process, but since our culture is respected and that there is no legal unnecessary immobilization can be a good way to increase the speed. For the last, there are some suggestions so that law students can think of legislative and administrative changes aimed at the balance between legal certainty and reasonable duration of the process